Development of Student Worksheets Based on Problem Based Learning Models to Improve Problem Solving Ability - Lintang, Luthfiah; Armanto, Dian; Mansyur, Abil (PARADIKMA: JURNAL PENDIDIKAN MATEMATIKA, 2023)
In order to enhance problem-solving abilities, this study intends to describe the validity, practicality, and effectiveness of student worksheets based on problem-based learning models. Analysis, Design, Development, Implementation, and Evaluation are the five stages of the ADDIE development paradigm, which is used for development research. Class VIII pupils from Medan State's 4 MTs Preparation for the academic year 2022/2023 served as the study's subjects. The findings revealed that: 1) problem-based learning worksheets for students were deemed valid with an average value of 4.06; 2) problem-based learning worksheets for students were deemed practical based on experts and the implementation of learning with the implemented category good; and 3) problem-based learning worksheets for students were deemed effective based on: a) classical completeness which reaches 84.00%, b) student response to learning is 93%, and c) increasing problem solving abilities based on N-Gain values of 0.50 is in the middle range.Keywords: Student Worksheets, Problem Based Learning Models, Problem Solving Ability